IN VITRO ANTICANCER (HELA), ANTI-INFLAMMATORY, BRINE SHRIMP LETHALITY ASSAY AND GC-MS ANALYSIS OF WHOLE PLANT ARCEUTHOBIUM OXYCEDRI (DWARF MISTLETOE) N-HEXANE FRACTION - Ashif Sajjad; Nazima Yousaf Khan; Jahangir Khan Achakzai; Muhammad Anwar Panezai; Inam ul Haq; Fouzia Noreen; Ayeesha Masood; Shazia Saeed; Sajid Nabi (Journal of Animal and Plant Sciences, 2023)
Mistletoe has been used for anticancer treatment in different parts of the world. Most of the chemotherapeutic drug molecules are isolated from mistletoe. The present study aims to comprehensively examined for the first-time whole extract and different fractions of Arceuthobium oxycedri (drawf mistletoe) belonged to Ziarat Juniper Forest of Balochistan, Pakistan. The whole plant extract and its different fractions were investigated for some biological activities such as: anticancer by MTT assay on HeLa cell line, Brine Shrimp Lethality by β-hatching technique and Anti-inflammatory by chemiluminescence technique in oxidative burst assay. The structural elucidation was done by GC-MS and a total of 21 compounds were identified. The whole plant A. oxycedriI, n-hexane fraction (WAOHF), exhibited 69.3% mortality against cervical cancer cell line (HeLa) with IC50 value of 11.4 ± 0.7. The brine shrimp lethality activity in WAOHF showed 53.3% mortality at highest concentration. The anti-inflammatory activity in whole plant A. oxycedri methanolic extract (WAOME), WAOHF and whole plant A. oxycedri aqueous fraction (WAOAF) were inactive. The obtained results revealed that the WAOHF exhibited significant anticancer against cervical cancer cell line (HeLa), which can be considered as an alternative therapeutic anticancer drug in future with least side effects.
Keywords: Arceuthobium oxycedri; Anticancer; Anti-inflammatory; Brine Shrimp Lethality; n-hexane fraction